2011
DOI: 10.1189/jlb.0411190
|View full text |Cite
|
Sign up to set email alerts
|

Plasmacytoid dendritic cells and cancer

Abstract: Cancer develops in a complex microenvironment comprising cancer cells, stromal cells, and host immune cells with their soluble products. The counteracting host-protective and tumor-promoting roles of different immune cell populations have been elegantly clarified in the last decade by pertinent genetically modified mouse models. Among cells with a potential role in cancer immunity, PDCs might represent important players as a result of their capacity to bring together innate and adaptive immunity. This review s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
103
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(106 citation statements)
references
References 138 publications
1
103
0
1
Order By: Relevance
“…By contrast, pDCs from the same patient cohort were significantly reduced in number, not only in an age-dependent but also in a cancer-related manner (Fig. 9c), in line with published observations 31,34,[37][38][39] . Concomitantly, we also found that either the ability to ingest tumour cell-derived apoptotic bodies (Fig.…”
supporting
confidence: 91%
See 3 more Smart Citations
“…By contrast, pDCs from the same patient cohort were significantly reduced in number, not only in an age-dependent but also in a cancer-related manner (Fig. 9c), in line with published observations 31,34,[37][38][39] . Concomitantly, we also found that either the ability to ingest tumour cell-derived apoptotic bodies (Fig.…”
supporting
confidence: 91%
“…By contrast, the capacity of CCR-derived pDCs to produce IFNa upon CpG stimulation was partially defective (Fig. 9f), as largely documented in patients with other carcinoma types 34,40,41 . Significantly, number and function (for example, cytokine production) of the slanDC contingent was maintained even in advanced disease stages (Fig.…”
mentioning
confidence: 56%
See 2 more Smart Citations
“…pDCs have been found in many human solid tumors, including lung cancer, and correlates to a poor patient prognosis (29). They are present in their nonactivated state and have been associated with the development and maintenance of the immunosuppressive tumor microenvironment (30).…”
Section: Discussionmentioning
confidence: 99%